المواقف الأمريكية من الثورة الجزائرية - نفطية , خوازم , سهيلة, نور الهدى (جامعة الوادي University of eloued, 2018)
تتناول هذه الدراسة موضوع المواقف الأمريكية من الثورة الجزائرية. وقبل الخوض في موضوع المواقف من الثورة تطرقنا إلى الموقف الأمريكي من المسألة الجزائرية قبل اندلاع الثورة. ففي الفصل التمهيدي بدأنا بالموقف الأمريكي من الاحتلال الفرنسي للجزائر ومنها ذهبنا إلى ذكر لاتصالات قادة العمل الوطني بشخصيات أمريكية رسمية فذكرنا كلاًّ من "الأمير عبد القادر" ومن بعده حفيده "الأمير خالد" ثم "فرحات عباس" وجماعته, والموقف الأمريكي من القضية الجزائرية قبل اندلاع الثورة التحريرية وتمثلت في الموقف من مجازر الثامن ماي 1945, وتضمن الفصل الأول دراسة للمواقف الأمريكية الرسمية تجاه الثورة الجزائرية وينقسم إلى مبحثين؛ تناولنا في المبحث الأول المواقف الأمريكية الرسمية المعادية للثورة و المدعمة للطرف الفرنسي ومنها ذهبنا إلى إبراز المساعي الجزائرية في محاولة لتحييد الطرف الأمريكي في النزاع, أما المبحث الثاني فيتناول المواقف الأمريكية الرسمية المساندة للثورة الجزائرية. أما الفصل الثاني فعُني بدراسة المواقف غير الرسمية وهو بدوره يشمل مبحثين: تضمن الأول مواقف التنظيمات الطلابية والنقابات العمالية الأمريكية وتضمن المبحث الثاني ردود الفعل من قيام الثورة الجزائرية من خلال الصحافة الأمريكية. "Summary: This study deals with the American attitudes towards the Algerian revolution. Before going into the subject of attitudes from the revolution, we discussed the American position on the Algerian issue before the revolution. In the introductory chapter, we began with the American position from the French occupation of Algeria, and from there we went to mention the contacts of national business leaders with official American figures. We mentioned both Prince Abdul Qadir and his grandson Prince Khaled and then Farhat Abbas and his group, and the American position on the Algerian issue before the outbreak. The liberation revolution was the position of the massacres of May 8, 1945 The first chapter examines the official American positions towards the Algerian revolution and is divided into two topics. In the first section, we discussed the official American positions which are anti-revolutionary and supported by the French party, and we went to highlight the Algerian efforts in an attempt to neutralize the American side in the conflict. The second section deals with the official American positions supporting the revolution The algerian. The second chapter deals with the study of informal positions, which in turn includes two topics: The first included the positions of the student organizations and the American trade unions. The second topic included reactions from the Algerian revolution through the American press."
مذكرة ماستر تخصص تاريخ المغرب العربي الحديث والمعاصر
Keywords: الكلمات المفتاحية: المواقف الامريكية، الثورة الجزائرية، رسمية وغير رسمية.; Mots-clés: Attitudes américaines, Révolution algérienne, officielle et informelle.; Keywords: American attitudes, Algerian Revolution, official and informal.